Knee osteoarthritis among ex-professional male soccer players compared to non-athletes - Sayed Sadredin Shojaedin; Hossein Mehrabian; Ebrahim Mohammad Ali Nasab; Mehdi Erfani (Vesnu Publications, 2012)
Introduction: The advantages of physical activities have recently been recommended in preventing such chronic diseases as osteoarthritis. However, the risks that severe physical activity may have on musculoskeletal system of athletes are still unknown. The purpose of this study was to compare the radiographic grading scales of osteoarthritis, knee pain, existing symptoms, physical functions in activities of daily living, sports and recreation, and the quality of life of ex-elite soccer players with the same factors in non-athlete controls. Materials and Methods: 15 ex-elite male soccer athletes and 15 non-athletes were purposefully selected in this study. The clinical and radiological methods (Kellgren-Lawrence) along with an internationally-known and translated questionnaire called "Knee Injury and Osteoarthritis Outcome Score" (KOOS) were used to diagnose the disease. Statistical analysis of data was performed via independent t test at significance level of P ≤ 0.05. Results: Mean scores of radiographic grading scales for osteoarthritis of the knee (P = 0.001) was significantly higher in ex-professional athletes than in non-athlete controls. There was, however, a significant lower mean scores of knee pain (P = 0.002), symptoms (P < 0.001), physical function in daily activities (P = 0.001), sport, recreation (P < 0.001) and quality of life (P < 0.001) in athletes as compared to non-athletes. Conclusion: Having a professional soccer-playing career can result in high risk of knee osteoarthritis in former elite athletes. Keywords: Knee osteoarthritis, Soccer, Ex-elite retiree